Evaluating and Analyzing the Solar Public Street Lighting Utilization: A Case Study in Manokwari - Padang, Bernat Ruba Sampe; Mulyadi, Rosady; Yusran, Yusran (Indonesian Journal of Multidisciplinary Science, 2023)
Public Street Lighting (PSL) is one of the complementary road buildings used to illuminate the road. Solar Public Street Lighting (SPSL) is used in several places in Indonesia. Based on the background above, the objectives of this study are (1) to obtain the results of technical analysis of SPSL, (2) to obtain the results of economic analysis of SPSL development using investment schemes. The research was conducted in Manokwari Regency, West Papua. The research data were obtained from the results of measurements on solar panels to solar charge controllers and measurements from solar charge controllers to batteries in sunny, cloudy or rainy weather conditions from 08:00 WIT to 17:00 WIT. Economic analysis is carried out to obtain the parameters of Net Present Value (NPV), and Benefit Cost Ratio  (B/C Ratio) with discount rates of  10% and 0%. The results showed that (1) based on technical analysis SPSL in Manokwari Regency has met public street lighting standards, in accordance with  the Minister of Transportation Regulation No. 27 of 2018 concerning street lighting equipment. (2) An economic analysis shows that the development of SPSL with investment schemes is not feasible because the NPV value  < 0 with an IRR of 10%, and a B/C Ratio of < 1. The construction of SPSL is economically feasible if the calculation of 0% IRR with the price of electricity per kWh reaches a value of IDR 14,411.32 or approximately ten times the price of Non-Subsidized PLN kWh electricity which is worth IDR 1,444.70.